Objective climate classification of Slovenia. (29th March 2017) - Kozjek, Katja; Dolinar, Mojca; Skok, Gregor
ABSTRACT: In the study, the climate regions of Slovenia were determined. The regionalization was based on the gridded climate data for the reference period 1981–2010. The climatic regionalization was performed predominately objectively with a combination of two statistical methods; the factor analysis which was followed by k ‐means clustering. With the use of factor analysis the initial number of 31 climate variables was reduced to four variables or factors, which comprised the input for the cluster analysis where Slovenia was divided into six climate regions: Submediterranean climate region, Wet climate of hilly region, Moderate climate of hilly region, Subcontinental climate region, Subalpine climate region and Alpine climate region. Compared to previous climatic regionalization studies for Slovenia, the presented study uses a higher degree of objectivity in the determination of the extent and borders between climate regions. The current study was based purely on climate data, while in the previous studies, the borders were defined more subjectively, based on the authors' expertise of local climate.